The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2139/ssrn.2079314
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand Corporate Boards in Transition: Composition, Activity and Incentives between 1995 and 2010

Abstract: We document, describe and interpret changes in New Zealand corporate board characteristics between 1995 and 2010, a period centred around the 2003 introduction of the NZX Corporate Governance Best Practice Code. Unsurprisingly, the representation of non-executive, independent and female directors on NZ boards rose during the period, as did real chair and director fees and the importance of board committees, while average board size fell. Perhaps more surprisingly, much of this movement occurred before 2003. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…Thus, the number of non‐prestigious MDS is more than twice the number of prestigious MDS, showing that the majority of MDS on NZX boards are from non‐prestigious companies. This confirms a unique pattern of MDS in New Zealand, where directors usually hold a higher proportion of directorships in non‐listed companies relative to listed companies (Boyle and Ji, 2013; Li, 2013; Brown and Roberts, 2016).…”
Section: Methodssupporting
confidence: 55%
“…Thus, the number of non‐prestigious MDS is more than twice the number of prestigious MDS, showing that the majority of MDS on NZX boards are from non‐prestigious companies. This confirms a unique pattern of MDS in New Zealand, where directors usually hold a higher proportion of directorships in non‐listed companies relative to listed companies (Boyle and Ji, 2013; Li, 2013; Brown and Roberts, 2016).…”
Section: Methodssupporting
confidence: 55%
“…Accurate composition of the board is essential to provide diverse perspectives. Boyle and Ji (2011) argued that greater female representation on boards provide some additional skills and perspectives that may not be possible with all-male boards. According to Robinson and Dechant (1997) The objective of appointing an Independent director in a company is to enhance adherence to corporate governance.…”
Section: Board Size and Performancementioning
confidence: 99%
“…In addition, larger boards provide greater monitoring and advice (Adam & Mehran, 2003;Anderson, Mansi & Reeb, 2004;Coles, Daniel & Naveen, 2008). Further, Boyle and Ji (2011) reported that the average board size fell from about 6.6% directors in 1995 to 5.9% in 2010, and that this decline is significant at the 1% level. Therefore, increasing the board size is able to deal with the agency problem by alignment of interests of shareholders and directors and improve firm performance.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly there are issues of whether there is a significant impact of both owner and non-owner managers' presence in the board on agency costs. Boyle and Ji (2011) report that the average board size in New Zealand-listed firms was about 5.9 directors in 2010. Compared with the US (Ning et al, 2010), the UK (Guest, 2009), and Australia (Kang, Cheng &Gray., 2007), the board size in New Zealand firms is noticeably smaller, but this reflects the smaller size of NZ firms.…”
Section: Introductionmentioning
confidence: 99%